3x-5x-3=

Simple and best practice solution for 3x-5x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5x-3= equation:


Simplifying
3x + -5x + -3 = 0

Reorder the terms:
-3 + 3x + -5x = 0

Combine like terms: 3x + -5x = -2x
-3 + -2x = 0

Solving
-3 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -2x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -2x = 0 + 3
-2x = 0 + 3

Combine like terms: 0 + 3 = 3
-2x = 3

Divide each side by '-2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 156=6(-6n+8) | | -112=-4+6b | | 2+2/5(x+1)=x-(2x+3)/5 | | 7a+3a+5b+11b= | | 2x^2+10x+13=0 | | (4i)/(4-i) | | -82=m+2(-6m-8) | | 6(2X+1)=252 | | X=10cosx | | g(x)=x+14 | | 2345678347756846876427867478968763276878684348237682764878736+73642675682385678482486747= | | g(y+6)= | | (3x-1)/4-2x+1/5=(7x-13)/20 | | 32+5=2x+13 | | 0=1.5x^2-8x+8 | | 2x+4x+3y-y= | | -3m+1=9-15 | | 104=2(x+16)+x | | r=1/3d(60-t) | | -5x-4=16+x | | 2x+40=4x+22 | | D(t)=4.9t^2-0.1t^3 | | 8x+204=6x+180 | | |2-5|= | | 3(2n+4)=30 | | 6x-16=104 | | 7-9z=81+z | | 4x^2-19x+17=-6x+7 | | 4r+(7*4)=72 | | 3a-5=18 | | F(x)=4x-3x^2-x^3 | | D(t)=4.9t^2 |

Equations solver categories